FACTORS INFLUENCING SUCCESSFUL MANAGEMENT OF DENTURE-RELATED LESIONS IN ELDERLY PATIENTS - Anandita Riska, Pratiwi; Ratna Kumala, Indrastiti; Anandina Irmagita , Soegyanto (Fakultas Kedokteran Gigi Unjani, 2024)
The denture-related oral mucosal lesion is a heterogeneous clinical and histopathological tissue alteration commonly found among older people. Dental management requires understanding dental and medical aspects and paying attention to many other factors. A 62-year-old male came to Universitas Indonesia Dental Hospital complaining of painful soreness and redness at the corner of his mouth. The patient had hypertension and had not routinely taken Amlodipine in the last three years. A blood count examination revealed normal results, except for a slightly low MCV. Diagnosis of angular cheilitis was established along with denture stomatitis and median rhomboid glossitis. Angular cheilitis was healed after administration of 0.2% Miconazole cream. Unfortunately, the patient could not use the drug correctly, so denture stomatitis and median rhomboid glossitis have not entirely resolved yet. The predisposing factors of denture-related oral mucosal lesions might be local or systemic. Proper pharmacological treatment and appropriate dental health education will make a good prognosis. However, the patient's compliance and cooperation will determine the success of dental treatment. It is essential to enhance patient compliance and overcome the treatment challenges to achieve optimal results in managing denture-related oral mucosal lesions of elderly patients. DOI : 10.54052/jhds.v4n1.p35-46